COVID-19 in Madrid: Leading pandemic control after being the Spanish epicenter - Soriano, Vicente; Fernández-Montero, José V. (Permanyer Publications, 2022)
The arrival of coronavirus disease (COVID-19) in Europe exploded initially in North Italy and soon thereafter at several other major European cities, including Madrid. Indeed, Madrid was the epicenter of SARSCoV- 2 infection in Spain, with a dramatic surge of cases since mid-March 2020.
Keywords: COVID-19; Madrid; pandemic; Scopus(2); JCR